(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
This paper presents the issues of distance education, basic research on inclusive education and the current need for teacher training. The sudden «jump» from full-time distance learning has created a «collapse» in terms of inclusion. That is why our study considered: difficulties formation of inclusion and non-compliance and opportunities for all participants in the educational process; narrow orientation subjects and the lack of real practice for working with children with disabilities in the proposed training program for teachers; mismatch legal requirements and opportunities for schools to provide socialization and getting proper education of children with disabilities.During the collection and analysis of information, we used remote research methods, which included survey using Google forms; online meetings and interviews with teachers and teacher assistants; online discussions on the specifics of the proposed content and its adaptation to the needs of the inclusive class and for children with disabilities.According to the results of our research, we found some contradictions between the requirements for the creation of an inclusive educational space, the forms offered for distance learning, and the opportunities of participants in the learning process. It is possible to design and develop specialized courses for teachers working with children with disabilities.